Influência de diferentes tratamentos físico-químicos na adesão e viabilidade de fibroblastos de ligamento periodontal à superfície radicular simulando dentes avulsionados - Moreira, Camila Said [UNESP] (2016)
The delayed reimplantation of avulsed teeth is a reality in dental offices. In an attempt to restore architecture and function of the periodontal ligament, avoiding ankylosis, preventing or modulating the replacement resorption, avulsed teeth root surface may be treated with various substances including EDTA (ethylenediaminetetraacetic acid) to 17%, always seeking a lower chance of occurring inflammatory or replacement resorption. Thus, the aim of this study was to evaluate the effectiveness of the treatment of discs cutted of the vestibular surface of bovine teeth roots with EDTA 17% with Emdogain® with hyaluronic acid and collagen through cell viability tests, quantification of cytokines IL -1ß, IL-6, IL-8, IL-10 and TNF-α by ELISA assay and, in addition, it was taken Illustrations by scanning electron microscopy of the accession of fibroblasts on the dentin disks. 155 dentin discs with 4,5 mm in diameter will be cut from the vestibular surface of the root surface of bovine teeth, previously scraped or not with periodontal curette. The discs were regularized, cleaned and autoclaved. The specimens were treated with the substances advocated and placed in 96 well plates are seeded in which primary cell cultures of human periodontal ligament fibroblasts that were in contact with the discs for 48 hours. The survival and cell viability on the surface of the disks are evaluated by XTT assay. The scanning electron microscopy was used to verify adherence of fibroblasts to the surface of the discs. Detection and quantification of cytokines were done by ELISA assay. The data were statistically analyzed by ANOVA and Tukey (p < 0.05). The results showed that the use of 17% EDTA for 5 minutes without stirring was more effective than the other protocols (p <0.05) and combined with hyaluronic acid was less cytotoxic promoting better cell viability. It was not possible to ensure the fibroblasts display in scanning electron microscopy. As for the ELISA assay, there was expression of IL- 1β, IL -6 and IL -8 (pro- inflammatory cytokines), but there was just statistically significant difference between IL -6 and IL -8. Thus, we can conclude that 17% EDTA for 5 minutes without stirring and hyaluronic acid showed less cytotoxicity index fibroblasts of the periodontal ligament, but there was inflammatory response by IL -6 and IL-8 expression .